Aletheiana tenella, a new genus and new species of freshwater hymenosomatid crab (Crustacea: Decapoda: Brachyura) from Central Sulawesi, Indonesia - Ng, Peter K. L.; Lukhaup, Christian (Zootaxa, 2015)
A new genus and new species of free-living hymenosomatid crab, Aletheiana tenella, is described from Central Sulawesi, Indonesia. The two known Sulawesi hymenosomatid species, Cancrocaeca xenomorpha Ng, 1991, and Sulaplax ensifer Naruse, Ng & Guinot, 2008, are both from cave habitats. Aletheiana gen. nov. is most similar to Neorhynchoplax Sakai, 1938 (from freshwater and intertidal habitats in the Indo-West Pacific), and Sulaplax, but can be distinguished by its front possessing only one subventral rostral lobe, the base of the antenna is positioned between the base of the ocular peduncle and antennular fossa, the posterior margin of the epistome has two low, rounded median lobes, the merus of the third maxilliped is elongated, the ambulatory dactylus has a prominent subdistal spine, the cutting edges of the chela are armed with distinct teeth proximally, and the male abdomen is slender and elongate with the telson linguiform.